Molecular Characterization of Sexual Diversity in a Population of Serpula lacrymans, a Tetrapolar Basidiomycete - Skrede, Inger (Genetics Society of America, 2013)
Different mating systems have evolved in the fungal kingdom, including a tetrapolar multiallelic mating system in many basidiomycetes. In tetrapolar species, the presence of different alleles at two mating loci (MAT A and MAT B) is necessary for mating to occur. The tetrapolar fungus Serpula lacrymans causes wood-decay in buildings in temperate regions worldwide and is present in Europe with a genetically homogeneous founder population. Using genome sequence data, we annotated the two mating type loci for S. lacrymans and found the expected synteny with other basidiomycetes, except for a retrotransposon being present in one locus (MAT A). We developed markers linked to the MAT A and MAT B regions and used these to investigate the mating type diversity in the European population. Moreover, we found a good match between the genetic markers and functional mating types as revealed by segregation and mating studies. A low diversity of mating types is present in the European S. lacrymans population caused by the founder event where a limited number of genotypes were introduced. This finding contrasts the situation in natural fungal populations where a high diversity of mating types is normally present. Although S. lacrymans has a large and viable population in Europe, we argue that the low mating type diversity restrains the dispersal and establishment of the fungus.